Efektivitas Pengendalian Biaya Operasional Pada PT. Berkat Jaya Pangestu Medan - Rahmad Gusrifa (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The purpose of this study was to determine whether the control carried out at PT. Thanks to Jaya Pangestu Medan, it has been effective in using operational costs and what factors cause deviations in the operational cost budget. In this study using a descriptive research approach, namely a study to compile, classify, interpret and interpret data so as to provide an overview of the problem of analyzing the effectiveness of operational cost control. The data analysis technique used a descriptive accounting approach. Based on the results of data analysis and discussion, it can be seen that the effectiveness of operational cost control applied by PT. Thanks to Jaya Pangestu, Medan was running less effectively. Operational cost control by every field in the company has not been in accordance with the company's target where there is a deviation from the operational cost with the budgeted exceeding the company standard of 5%. The factors that cause high operational costs are the increase in the company's operational activities including employee costs, general costs, marketing costs, HR development costs, interest costs and other funds and depreciation costs.